Superparamagnetic Iron Oxide Decorated Indium Hydroxide Nanocomposite: Synthesis, Characterization and Its Photocatalytic Activity - C. Y. Chong; T. H. W. Lee; J. C. Juan; Mohd Rafie Johan; C. F. Loke; K. H. Ng; J. C. Lai; Teck Hock Lim (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
A simple and scalable liquid-based method was developed to produce a nanocomposite photocatalyst which was comprised of Fe3O4 nanoparticles (4-5 nm) decorated indium hydroxide nanorods (mean width 33 nm and average aspect ratio 2-3). The nanocomposite was produced at 25 ℃ in water via a hydroxide-induced co-precipitation ensued by a cathodic reduction during which the non-magnetic Fe(OH)3 intermediate was reduced to magnetic Fe3O4 at 20 V within 1 h. The incorporation of Fe3O4 nanoparticles served to bestow magnetic recoverability to the photocatalyst and helped enhance visible light absorption simultaneously. Interestingly, the addition of Fe3+ led to the formation of In(OH)3 nanorods rather than the commonly observed nanocubes. In comparison to the In(OH)3 system having a band gap of 4.60 eV), the band gap of the Fe3O4/In(OH)3 nanocomposite produced was determined to be 2.85 eV using the Tauc’s plot method. The effective reduction in band gap is expected to allow better absorption of visible light which in turns should help boost its photocatalytic performance. The Fe3O4/In(OH)3 nanocomposite was structurally characterized using a combination of PXRD, FESEM, EDS, and TEM and its paramagnetic property was proven with a positive mass susceptibility measured to be 1.30´10−5 cm3.g−1. Under visible light, a photocatalytic degradation efficiency of 83% was recorded within 1 hr for the nanocomposite using methylene blue as a dye. The photocatalytically-active Fe3O4/In(OH)3 should have good potential in visible-light driven waste water degradation once further optimized. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).